Praktik Wacana Warganet dalam Melakukan Kontrol Sosial melalui Konten Video di Media Sosial - Yuki Jauza Hasna Afyadi; Alex Sobur (UNISBA Press, 2024)
Abstract. The era of 5.0 is entering where technology has a big role in helping people carry out various social activities, including communication. One of these communication technologies is social media. In 2023, the public was surprised by a video created by a TikTok influencer named Bima Yudho Saputro who criticized the city of Lampung as an undeveloped city. Researchers were interested in this phenomenon and conducted research using qualitative methods and Fairclough's critical discourse approach. This research aims to find out how the discourse practices carried out by netizens in implementing social control through the content of the criticism video